Explanatory factors of local waste management in Morocco: a territorial and organizational approach - Sadik, Mohammed; Chnigri, Yousra; Slimani, Hamid (Business, Management and Economics Engineering, 2023)
Purpose – The aim of this article is to specify the determining factors behind the decision to adopt either an internal or external means of the household waste management service in Moroccan local authorities (LAs), particularly in the “communes”. Research methodology – The methodology applied is quantitative, based on a questionnaire addressed by e-mail to 115 “Communes”. The SPSS 25 software was used to analyze the result of the logistic regression. Results – Our findings show that socio-territorial factors do not have a significant influence upon the choice of a local waste management service delivery mode, while organizational and institutional factors, particularly financial resources, do influence this choice. Local authorities with better financial resources tend to rely less on in-house solid waste management services. Research limitations – Methodological limitations such as sample size and a lack of reliable data on public service delivery, may be overcome in an exploratory study by using a qualitative method (interviews, case studies). Practical implications – Our study sheds light on the factors explaining the development of public service management methods as well as testing proposals favoring the effective use of management techniques in the local context. Originality/Value – The originality of our study lies in its quantitative investigation of waste management service delivery mode in Moroccan local authorities emphasizing the role of financial resources and distinguishing itself from previous research by finding that socio-territorial factors do not significantly affect this choice.